Bacteriophage SPO1 protein Gp46 suppresses functions of HU protein in Francisella tularensis - Spidlova, Petra; Sokolova, Eliska; Pavlik, Pavla (Frontiers in Microbiology, 2023)
The nucleoid-associated protein HU is a common bacterial transcription factor, whose role in pathogenesis and virulence has been described in many bacteria. Our recent studies showed that the HU protein is an indispensable virulence factor in the human pathogenic bacterium Francisella tularensis, a causative agent of tularemia disease, and that this protein can be a key target in tularemia treatment or vaccine development. Here, we show that Francisella HU protein is inhibited by Gp46, a protein of Bacillus subtilis bacteriophage SPO1. We predicted that Gp46 could occupy the F. tularensis HU protein DNA binding site, and subsequently confirmed the ability of Gp46 to abolish the DNA-binding capacity of HU protein. Next, we showed that the growth of Francisella wild-type strain expressing Gp46 in trans corresponded to that of a deletion mutant strain lacking the HU protein. Similarly, the efficiency of intracellular proliferation in mouse macrophages resembled HU protein is inhibited by Gp46 2 that of the deletion mutant strain, but not that of the wild-type strain. These results, in combination with findings from a recent study on Gp46, enabled us to confirm that Gp46 could be a universal inhibitor of HU proteins among bacterial species.